Corporate governance in China - Chen, Jian, 1962 February 6- (London ; New York : RoutledgeCurzon, 2005)
This book examines key questions relating to corporate governance in China, including the relationship between ownership structure and corporate performance, the determinants of capital structure, and the nature of contemporary governance structures.
Introduction -- Theoretical approaches to corporate governance -- The evolution of corporate governance in China -- The effect of ownership structure on the underpricing of initial public offerings -- Ownership structure as a corporate governance mechanism -- The determinants of capital structure -- Chinese corporate groups : a perspective from governance structure -- General conclusions and future work.
Includes bibliographical references (pages 153-169) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Corporate governance -- China; Industrial policy -- China; Gouvernement d'entreprise -- Chine; Politique industrielle -- Chine; BUSINESS & ECONOMICS -- Industries -- General; Corporate governance -- China; Industrial policy -- China; Corporate governance; Industrial policy; China